THE INCREASED SAFETY JELLY DISHES FOR SCHOOL FEEDING - Galina Valentinovna Ivanova; Aleksandra Nikolaevna Ivanova (Современная наука и инновации)
In our days there are a high demands for schoolfeeding. Student must have a good and high-quality food. Student must be confident incomplete safety of its food.The main object of our work is the development of safe food for schoolchildren. Jelly cannot be used in school meals. We used the Cetraria islandica for making sweet dishes and jelly. These desserts have good microbiological characteristics. Broth Cetraria islandica reduces the growth bacteria Escherichia coli and Staphylococcus aureus thus makes sweet dishes safety in healthiness point of view.